INDEPENDENT LEARNING IN ENGLISH ONLINE CLASS DURING COVID-19 PANDEMIC: STUDENTS PERCEPTIONS AND ITS CHALLENGES - Andi Mukarramah Nagauleng; Ahmad Mustamir Waris (University of Kuningan, 2022)
The spread of Covid-19 in Indonesia forces teachers and students to conduct the online learning-teaching process independently. Online learning is carried out to protect teachers-students and reduce the number of people affected by the virus. Thus, this present study aims to discuss how independent learning in online English class put into practice at school, discover students’ perceptions of independent learning in online English classes and its challenges during the Covid-19 pandemic. This present study relays on mixed methods research design. Qualitative and Quantitative data were collected through a survey using a google form. Qualitative data were analyzed by coding, classifying, explaining, and concluding. Meanwhile, quantitative data were analyzed using the Likert scale method through SPSS ver. 23. The results show that in the learning-teaching process during the covid-19 pandemic, students learn independently using learning-teaching materials provided by English teachers. Besides, students use media such as YouTube to help them understand the material given by teachers. Students claim that independent online English learning is ineffective since students find difficulties in understanding materials. Although students use technology to support the learning-teaching process, it does not work well since the internet connection is unstable and internet quotas are limited. Therefore, teachers should manage independent online learning properly to enable students to achieve the goal of the learning-teaching process. Teachers should organize and control the learning-teaching process according to current needs; planning, implementation, and assessment.